2015
DOI: 10.1515/med-2015-0096
|View full text |Cite
|
Sign up to set email alerts
|

Canine transmigration accompanying mandibular retrognathism secondary to osteitis

Abstract: Transmigration is a tooth pathology in which the migrating tooth bud passes the median plane. Methods: This study is a presentation of the diagnostic and therapeutic outcomes in the cases of 4 stomach teeth transmigrations diagnosed in 3 patients with mandibular retrognathia which was a complication after osteitis in the postnatal period and infancy. Results: Extending imaging diagnostics to include CT, most preferably CBCT, makes it possible to precisely evaluate a transmigrated canine’s position and to plan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(27 citation statements)
references
References 18 publications
1
22
0
4
Order By: Relevance
“…Apart from case reports and cohort studies, no other design was found during the search. After the exclusion criteria had been met, 12 full-text articles (Cavuoti et al, 2016;Jaisinghani et al, 2019;Koszowski et al, 2015;Northway, 2019;Peerlings, 2010;Plaza, 2016;Shukla et al, 2019;Sinko et al, 2016;Üçüncü et al, 2011;Vaida et al, 2014;Vera-Guerra et al, 2019;Wertz, 1994) remained to be retrieved and examined for further evaluation. The characteristics of the included studies are summarized in Figure 1, and the key findings about the orthodontic biomechanics and clinical considerations were collected and are summarized in Tables 3 and 4.…”
Section: Search Strategy and Eligibility Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…Apart from case reports and cohort studies, no other design was found during the search. After the exclusion criteria had been met, 12 full-text articles (Cavuoti et al, 2016;Jaisinghani et al, 2019;Koszowski et al, 2015;Northway, 2019;Peerlings, 2010;Plaza, 2016;Shukla et al, 2019;Sinko et al, 2016;Üçüncü et al, 2011;Vaida et al, 2014;Vera-Guerra et al, 2019;Wertz, 1994) remained to be retrieved and examined for further evaluation. The characteristics of the included studies are summarized in Figure 1, and the key findings about the orthodontic biomechanics and clinical considerations were collected and are summarized in Tables 3 and 4.…”
Section: Search Strategy and Eligibility Criteriamentioning
confidence: 99%
“…The resources found for diagnosis and etiology were clinical examination and additional images, such as panoramic cephalometric radiographs (Cavuoti et al, 2016;Jaisinghani et al, 2019;Northway, 2019;Peerlings, 2010;Shukla et al, 2019;Üçüncü et al, 2011;Vera-Guerra et al, 2019;Wertz, 1994) and computed tomography (CT) images (Koszowski et al, 2015; Legend: CR: case report; yo: years old; y: years; m: month; PC: permanent lower canine tooth; DC: deciduous lower canine tooth; A/N; alignment and leveling; ML: metallic ligature; GL: gold ligature; TAD's: temporary anchorage devices. Source: Authors.…”
Section: Clinical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment options for transmigrated lower canines include autogenous transplantation, orthodontic traction, and radiographic observation [3,7,10,[24][25]. Impacted teeth can cause external radicular scarring and may damage adjacent teeth; thus, radiographic monitoring is indicated [26].…”
Section: A) B)mentioning
confidence: 99%